Lexical Representation of Olfactory Semiotics in Worldview of Yakut Language - R. P. Ivanova; T. L. Verkhoturova; E. N. Afanasyeva (Научный диалог)
The article is devoted to the exploration of additional semiotic meanings developed by olfactory perceptual lexicon in the Yakut language. The study analyzes lexicographic data on the vocabulary of olfactory perception, as well as the mechanisms of creating a cognitive-semiotic space of a text using this lexicon based on N. A. Lugynov’s work “Ulatyy keme” (“Time of Change”). Smell is consider ed by the authors as a cognitive-linguistic category, representing in the Yakut language not only the physiological aspect of sensory interaction with the world, but also a broad linguistic and cultural context that expresses the sign function of social, everyday, aesthetic, etc. status. The data from translating and explanatory dictionaries of the Yakut language were processed using classical methods of analyzing dictionary definitions, taking into account the elements of distribution of the studied lexical units. As a result of the study, it was established that the perceptual lexicon of olfactory perception, which allows describing smells as signs-indexes in the system of the Yakut language, implements an additional cognitivesemiotic function of signs-symbols in artistic discourse, revealing the internal state of a person, their socio-domestic relationships in society, attitude towards moral and ethical values and life.